Mechanistic Insights into Propolis in Targeting Type 2 Diabetes Mellitus: A Systematic Review - Wong, Chee Ning; Lee, Siew-Keah; Liew, Kai Bin; Chew, Yik-Ling; Chua, Ang-Lim (Planta Medica, 2025)
Type 2 diabetes mellitus (T2DM) is a major global health concern characterized by insulin resistance and impaired glucose metabolism. Growing interest in natural therapies has led to the exploration of propolis, a resinous bee product, for its potential anti-diabetic effects. This review examines the mechanisms by which propolis may aid in T2DM management. A literature search was conducted in SCOPUS and PubMed using the terms (Propolis) AND (diabetes OR “insulin resistance” OR hyperglycemia), focusing on studies published from 2014 onwards. The search yielded 384 and 207 records in SCOPUS and PubMed, respectively. After screening and full-text review, 42 studies met the inclusion criteria. Key variables analyzed included the type and source of propolis, experimental models, dosage, treatment duration, and primary and secondary outcomes. Findings highlight multiple mechanisms through which propolis may benefit T2DM, including enhancing pancreatic β-cell function, improving insulin sensitivity, regulating glucose and lipid metabolism, modulating gut microbiota, and reducing oxidative stress and inflammation. Some studies also reported protective effects on renal and hepatic function. Overall, propolis exhibits promising potential as a complementary therapy for T2DM. However, further well-designed clinical trials are necessary to confirm its efficacy, determine optimal dosing, and identify key bioactive compounds responsible for its therapeutic effects. Future research should focus on optimizing its clinical application for diabetes management.
Keywords: Apiculture; propolis; bee glue; diabetes mellitus; hyperglycemia; insulin resistance